On Generalized Heisenberg Groups: The Symmetric Case - Kritsada Sangkhanan (2018)
© 2018, Springer International Publishing AG, part of Springer Nature. In the literature, the famous Heisenberg group is the group of matrices of the form (1xz01y001),where x, y, and z are real numbers. In the present article, we examine a generalized Heisenberg group, obtained from an R-module M endowed with an R-bilinear form β, where R is a ring with identity. We show that the structure of the generalized Heisenberg group and its generating space are intertwined. In particular, we prove that if β is symmetric, then the corresponding Heisenberg group possesses an involutive decomposition into subgroups, which eventually becomes the semidirect product of groups. This leads to a better understanding of the algebraic structure of the generalized Heisenberg group as well as its extensions by subgroups.